Occurrence of cystacanths of Polyacanthorhynchus kenyensis larvae (Acanthocephala) in four teleostean fishes from a tropical lake, Lake Naivasha, Kenya - Aloo, P A; Dezfuli, B S (Folia parasitologica, 1997)
From January 1992 to December 1993, a total of 2158 fish, namely Oreochromis leucostictus (Trewavas, 1983), Micropterus salmoides (Lacépède, 1802), Tilapia zillii (Gervais, 1848) and Barbus amphigrama (Boulenger, 1902) were sampled from thirteen stations on Lake Naivasha, Kenya, using a fleet of gill nets and examined for helminth parasites. The prevalence of infection due to cystacanths of an acanthocephalan, Polyacanthorhynchus kenyensis Schmidt et Canaris, 1967 among parasitized O. leucostictus ranged from 30.4 to 86.9%; among T. zillii from 4.1 to 77.7%; in M. salmoides from 20 to 50%; and in B. amphigrama from 5.8 to 100%. In 735 hosts belonging to the above four species, a total of 4198 immature specimens of P. kenyensis were recovered. All cystacanths were found in extraintestinal sites, either free within the fish body cavity or encysted within the host visceral organs. There was no significant variation in the prevalence of the parasite within months (P > 0.001). Host sex ratio was significant (P < 0.001) in favour of male T. zillii, and also highly significant (P < 0.001) in favour of male O. leucostictus. Moreover, in this fish, prevalence of infection was observed to increase with the increase in the size of the fish. Among infected M. salmoides, there was no significant departure from a 1:1 sex ratio.
Keywords: Seasons; Prevalence; Acanthocephala; mužské pohlaví; prevalence; Helminthiasis, Animal; Kenya; helmintózy zvířat; Keňa; ženské pohlaví; zvířata; nemoci ryb; Tilapia; Fish Diseases; Fishes; ryby; Female; roční období; Male; Animals